Pengaruh Kualitas Layanan Terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah Dengan Citra Perusahaan Sebagai Variabel Moderating (Studi Kasus Pada PT. Bank BRI Persero Tbk.Cabang Tenggarong) - Deri Pranoto; Mawardi Mawardi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2021)
Abstract: The purpose of this study was to determine the effect of service quality on customer loyalty and to determine the effect of service quality on customer satisfaction at PT. Bank BRI Tenggarong Branch. As one of the state-owned banks with the largest profits in Tenggarong District, the problems that occur in Bank BRI are the Marketing Research Indonesia Survey (MRI) on customer loyalty and The Best Bank Service Excellence 2016 to 2017 shows that Bank BRI's score in terms of service and customer loyalty is still far from expectations. This means that Bank BRI has not succeeded in creating and managing customer loyalty properly. This study uses data analysis using Structural Equation Modeling (SEM) assisted by SmartPLS version 3.2.8. by testing the hypothesis using the t statistical test. The number of samples used amounted to 143 people. The results showed that the service quality variable had a significant effect on customer loyalty. The service quality variable has a significant effect on customer satisfaction. The variable of customer satisfaction has a significant effect on customer loyalty. The corporate image variable has no significant effect on customer loyalty. The service quality variable indirectly has a significant effect on customer loyalty through customer satisfaction so that the customer satisfaction variable is partially proven or there is partial mediation and the corporate image variable has no significant effect in moderating the customer satisfaction variable on customer loyalty with a positive relationship direction (strengthening) and the image variable. companies in this study are included in the Moderation Potential type (Homologiser Moderator) Keywords: Service Quality, Customer Loyalty, Customer Satisfaction, Satisfaction Customers, Company Image